1998
DOI: 10.1063/1.1148722
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and design of a superconducting eddy current probe for nondestructive testing

Abstract: Numerical modeling studies were carried out for the design and performance evaluation of an eddy current probe for superconducting quantum interference device (SQUID) based noncontacting electromagnetic nondestructive testing. The probe utilizes high-Tc SQUID from electromagnetic interference and to focus magnetic flux due to the eddy current excitation coil into the object under test (OUT). This is very important in order to achieve “self-nulling,” where the probe responds only to the defects in the OUT. Simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The similarity in the depth dependence between the defect ®eld and the eddy current was owing to the fact that the defect ®eld is caused by the dierence in the eddy-current distribution between the ¯awed and the un¯awed sample. The defect ®eld is generated by the current anti-dipole [4] at the position of the ¯aw. Hence, the depth dependence of the defect ®eld must be related to the depth dependence of the eddy-current density.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The similarity in the depth dependence between the defect ®eld and the eddy current was owing to the fact that the defect ®eld is caused by the dierence in the eddy-current distribution between the ¯awed and the un¯awed sample. The defect ®eld is generated by the current anti-dipole [4] at the position of the ¯aw. Hence, the depth dependence of the defect ®eld must be related to the depth dependence of the eddy-current density.…”
Section: Resultsmentioning
confidence: 99%
“…This dierence suggests that the conducting material surrounding the ¯aw has induced additional eddy currents due to the disturbed eddy current near the ¯aw, which has a non-negligible contribution to the defect ®eld. Therefore, for various excitation frequencies, it is inaccurate to calculate the phase of the defect ®eld with the current anti-dipole [4] without the contribution from the conducting material surrounding the ¯aw.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency of measurements and the configurations of the excitation coil, which are the essential parameters, have been widely described by several authors [9][10][11]. In particular, Kreutzbruck et al [12] reported on measurements using an HTS rf-SQUID and a circular excitation coil to measure artificial crack signals close to rivets in multilayer samples, maintaining a high dynamic range.…”
Section: Introductionmentioning
confidence: 99%